Assembly of eukaryotic photosystem II with diverse light-harvesting antennas. (August 2020) - Cao, Peng; Pan, Xiaowei; Su, Xiaodong; Liu, Zhenfeng; Li, Mei
Abstract : Photosystem II (PSII) catalyzes the light-driven oxygen-evolving reaction via its catalytic core and peripheral light-harvesting antennas. Oxyphototrophs have evolved diverse antenna systems, enabling them to adapt to different habitats. Recently, high-resolution structures of PSII-antenna supercomplexes from the green lineage (higher plants and green algae) and the red lineage (diatoms) were solved. The antenna complexes from the two lineages share similar protein folding, but differ in terms of the oligomeric states, pigment composition, and assembly patterns with the core. These differences result in distinct pigment–protein networks in PSII from different organisms. We herein summarize the similarities and differences in these structures and outline the molecular basis of the assembly, energy transfer, and regulation of the eukaryotic PSII-antenna supercomplexes.